The Influence of Halal Certification of MSMEs on Purchase Decision and Customer Loyalty in Bengkalis - Sari, Putri Ratna; rosa, nageeta tara (Politeknik Negeri Bengkalis, 2024)
This study aims to determine how much influence Halal Certification has on Purchase Decisions and Customer Loyalty in Bengkalis partially. study uses quantitative methods using probabilistic sampling technique based on the concept of random selection. The data collection technique was carried out using a questionnaire with a sample of 100 respondents, data processing using the IBM SPSS 25 application. The data analysis used is Descriptive Analysis, Classical Assumptions, Regression Analysis, T Test, and Coefficient of Determination. The results of this study indicate that: (1) There is a positive and significant influence between halal certification on purchasing decisions with a T value of 9,476 with a significance of 0,000. (2) There is a positive and significant influence between halal certification on customer loyalty with a value of is 7,752 with a significance of 0,000. The coefficient of determination on the halal certification variable on purchasing decisions is 47.8% and the halal certification variable on customer loyalty is 36.9%